Guidance note for peace-informed programming at the Green Climate Fund: Ecosystems and ecosystem services. - Scartozzi, Cesare M; Caroli, Giulia; Sarzana, Carolina; Läderach, Peter R.D.; Pacillo, Grazia; Hyslop, Daniel; Hahn, Andreas Luis; Azar, Elio; Nicatore, Giorgia; Brown, Oliver; Hassamal, Komal; Ehmsen, Simon (2023)
Implementing Ecosystem and Ecosystem Services (EES) projects in Fragile and Conflict-affected Settings (FCS) poses both operational challenges and the risk of inadvertently aggravating socio-political dynamics. The intertwined relationship between human, ecological, and economic systems makes these projects sensitive to conflict dynamics related to land access, environmental degradation, and livelihoods. Changes in ecosystems can be exploited by groups like political elites or armed entities, as observed in numerous case studies. Addressing ecosystem degradation offers opportunities for peace-promoting actions, including intercommunal dialogue. Despite their importance, ecosystem services are often undervalued by decision-makers, risking economic and social resilience. The guidance report further details the operational risks projects may face in FCS and emphasizes the importance of inclusive governance and conflict sensitivity.